THE EFFECTIVINESS OF CHEMICAL PRACTICUM KIT TO TRAIN SCIENCE PROCESS SKILL IN 10TH GRADE - Ningsih, Rani Kurnia; Hidayah, Rusly (JCER (Journal of Chemistry Education Research), 2019)
The purpose of this study was to obtain a chemical practicum KIT as an effective learning medium to train students' science process skills in scientific method, polar and non-polar covalent compounds, electrolyte and non-electrolyte solutions. This study uses a 4-D research model which includes the stages of defining, designing, developing, and distributing. However, in this study only limited to the development stage. The results of the research obtained showed that classical completeness in the posttest workmanship on all three materials was 100%. While the increase in learning outcomes aspects of science process knowledge and skills in the three materials are in the category of "medium" and "high". Based on the results, it can be concluded that the practicum KIT learning media is effective for training science process skills in scientific method, polar and non-polar covalent compounds, electrolyte and non-electrolyte solutions.